Penerapan Strategi Pembelajaran Information Search Terhadap Minat Belajar dan Hasil Belajar Kemampuan Membaca Pemahaman Pada Siswa Sekolah Dasar - Hermanto; Salito (Jurnal Pendidikan Dasar Islam, 2024)
This study aims to examine the impact of the Information Search strategy on students' learning interest and reading comprehension achievements in elementary schools. The Information Search strategy engages students in actively seeking information from various sources, designed to enhance their cognitive skills, critical thinking, and understanding of the learning materials. The research employs a quantitative approach with an experimental design. The results reveal that this strategy significantly improves students' learning interest, as evidenced by the questionnaire results before and after implementation. Additionally, students' reading comprehension achievements improved significantly, with the average score increasing from 70 to 85 after the treatment. The strategy also encourages active student participation in group discussions and resource utilization. Thus, the Information Search strategy can serve as an innovative alternative to enhance students' interest and learning outcomes, particularly in reading comprehension.